Safety and Efficacy of an Oxytocin Gel and an Equivalent Gel but Without Hormonal Ingredients (Vagivital® Gel) in Postmenopausal Women with Symptoms of Vulvovaginal Atrophy: A Randomized, Double-Blind Controlled Study - Fianu Jonasson A (Dove Medical Press, 2020)
Aino Fianu Jonasson,1 Marie Bixo,2 Inger Sundström Poromaa,3 Mikael Åstrom4 1Department of Clinical Sciences, Intervention and Technology, Division of Obstetrics and Gynecology, Karolinska Institute, Stockholm, Sweden; 2Department of Clinical Sciences, Obstetrics and Gynecology, Umea University, Umea, Sweden; 3Research Group; Reproductive Health, Department of Women’s and Children’s Health, Uppsala University, Uppsala, Sweden; 4StatCons, Malmo, SwedenCorrespondence: Aino Fianu JonassonDepartment of Clinical Science, Intervention and Technology, Division of Obstetrics and Gynecology, Karolinska Institute, Stockholm 171 77, SwedenTel +4670 483 60 28Fax +4608 31 11 01Email aino.fianu.jonasson@ki.sePurpose: The primary objective was to compare the efficacy of 12 weeks of daily treatment with Aqueous Hypromellose-based vaginal (Vagivital®) gel versus Aqueous Hypromellose-based vaginal gel plus 400 IU oxytocin gel in reducing the severity of the most bothersome vulvovaginal atrophy symptoms (MBS: itching, dysuria, bleeding, and pain/discomfort during vaginal sexual activity) observed at baseline. The secondary objectives were to evaluate the other vulvovaginal atrophy symptoms, vaginal pH, superficial squamous cells, and the safety and tolerability of both gels.Patients and Methods: This double-blind, randomized study evaluated the safety and efficacy of subjects randomly assigned to 12 weeks of daily intravaginal oxytocin gel (n=79) or Aqueous Hypromellose-based vaginal gel (n=78). The efficacy evaluation was performed using data from all included subjects who fulfilled entry criteria.Results: Both treatments induced statistically significant reductions in the severity of the MBS from baseline until 4 weeks (Vagivital mean reduction 0.90, p=0.0000; Oxytocin mean reduction 0.82, p=0.0000) and 12 weeks post baseline (Vagivital mean reduction 1.28, p=0.0000; Oxytocin mean reduction 1.16, p=0.0000), but the reduction of MBS severity was not significantly different between the treatment groups at either time point. No serious adverse events were reported in the Aqueous Hypromellose-based vaginal gel group during the treatment period, but one (breast cancer) was reported in the oxytocin gel group (assessed as unlikely related to the study compound).Conclusion: Significant reductions in the severity of the MBS were seen in both the Aqueous Hypromellose-based vaginal gel and the oxytocin gel groups, but with no significant differences in severity reduction seen between the groups. Both gels were safe and well tolerated. Given the benefits of avoiding the use of hormones, Aqueous Hypromellose-based vaginal gel is an attractive first choice in the treatment of postmenopausal women with vulvovaginal atrophy symptoms.Keywords: most bothersome vulvovaginal atrophy symptoms, MBS, non-hormonal therapy, dyspareunia, vaginal dryness